Perancangan dan Pembuatan Website E-Commerce Penjualan Kue Kering pada UD. Pawon Kue Surabaya - Nararindra Inggitasukma; Djoni Haryadi Setiabudi; Silvia Rostianingsih (Jurnal Infra, 2017)
Website e-commerce is the purchase and sale, marketing and services and delivery of products, services and information on the Internet and other networks, between companies networked with customers, suppliers, and other business partners through the website. This website is made for customers who stay away from UD. Pawon Kue Surabaya to see the product catalog, and make any product purchase transaction anytime and anywhere.In the website there are several features that can make easy for customers at UD. Pawon Kue Surabaya in making a purchase transaction. This application is created using the programming language HTML, PHP, JavaScript, and MySQL database. Web view using Bootstrap template.The final result of this website creation can search the list of products quickly, can make purchase transactions easily, and can know the status of the order easily. Owners can also view important reports such as income statements, sales reports, and product stock reports.